Evaluasi Pelaksanaan Pengujian Berkala Kendaraan Bermotor Menggunakan Metode Topsis di Unit Pengelola Pengujian Kendaraan Bermotor Pulogadung DKI Jakarta - sahara siti; Mukhamad Faizin (Universitas Negeri Jakarta, 2023)
The increasing population has an effect on the increase in the number of motorized vehicles. This has resulted in an increase in the rate of vehicle accidents. Vehicle accidents are also caused by vehicles that are not roadworthy. The role of UP PKB Pulo Gadung is very important in reducing the number of accidents caused by vehicles that are not roadworthy. In carrying out vehicle testing, it must be carried out in accordance with the standards set through the SOP that is carried out. But in reality the implementation does not always go according to the existing SOP. The purpose of this study was to determine the suitability of the implementation of vehicle testing services in the drive thru in lane, identification lane, mechanical lane and drive thru out lane. The method used is the topsis method with a quantitative descriptive approach. From the results of the study, it can be concluded that the standard of infrastructure facilities and competence of motorized vehicle periodic testers is an aspect that often becomes an obstacle in carrying out periodic motor vehicle testing